1989
DOI: 10.1111/j.1600-0714.1989.tb00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral hairy leukoplakia is not a specific sign of HIV‐infection but related to immunosuppression in general

Abstract: Oral hairy leukoplakia (HL) has been regarded as an early sign of HIV infection, and its clinical importance related to the poor outcome of the patients has been emphasized. Initially, HL was observed exclusively among male homosexuals, but subsequently demonstrated in all risk groups of HIV infection. The patient described in this article suggests that oral HL is not specific for HIV infection per se, but may be associated with immunosuppression also due to other causes. We describe an HIV-seronegative, heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 15 publications
1
50
0
1
Order By: Relevance
“…However, previous cases of OHL with hematologic malignancies have been reported in patients after chemotherapy, whose state of immunosuppression would be more severe than a malignancy per se 5,16,25 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, previous cases of OHL with hematologic malignancies have been reported in patients after chemotherapy, whose state of immunosuppression would be more severe than a malignancy per se 5,16,25 .…”
Section: Discussionmentioning
confidence: 96%
“…However, OHL has been reported in other immunosuppressed patients, including those with ulcerative colitis, pemphigus vulgaris, bullous pemphigoid, Behcet's syndrome, multiple myeloma, and leukemia 5,6,16,17,25 . Although rare cases of OHL in healthy people have been reported, OHL is believed to occur in immunosuppression as a rule 14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent individual reports have shown that the lytic cycle of EBV replication in OHL is not limited to immunocompromised patients under HIV infection (32). OHL is therefore not a specific sign of HIV infection, but is related to immunosuppression in general (33).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggest that the term 'oral hairy leukoplakia' should be abandoned, since it has a particular determined histological pattern [2] and this is not a premalignant one. Initially OHL was considered to be an oral pathognomonic sign of infection by human immunodeficiency virus (HIV), but the presence of this lesion in patients with other types of immune suppression has been described [3]. Nonetheless, cases of OHL in immunocompetent individuals have also been observed [4], although in the majority of these the presence of EBV has not been demonstrated.…”
mentioning
confidence: 99%